In vitro and in vivo genotoxicity assessment of gold nanoparticles of different sizes by comet and SMART assays. (October 2018) - Ávalos, A.; Haza, A.I.; Mateo, D.; Morales, P.
Abstract: Due to the increasing use of gold nanoparticles (AuNPs) in different areas such as medicine, biotechnology or food sector, human exposure to them has grown significantly and its toxicity evaluation has become essential. Therefore, the purpose of this study was to compare the potential genotoxic effects of 30, 50 and 90 nm AuNPs, using in vitro comet assay with the in vivo mutagenic and recombinogenic activity (SMART Test) in Drosophila . The results indicated that in both cell lines, 30, 50 and 90 nm (1–10 μg ml −1 ) AuNPs increased DNA strand breaks following 24 h treatment. This damage was not dose and size-dependent. Moreover, a modified comet assay using endonuclease III and formamidopyrimidine-DNA glycosylase restriction enzymes showed that in both cell lines, pyrimidines and purines were oxidatively damaged by all AuNPs, being 90 nm AuNPs slightly more genotoxic. However, the data obtained with SMART showed that 30 nm AuNPs did not modify the spontaneous frequencies of spots indicating lack of mutagenic and recombinogenic activity. Therefore, further experiments must be carried out to gain a better understanding of the mechanism of action of AuNPs to ensure their safe use. Highlights: The three AuNPs (30, 50 and 90 nm) induced strand breaks and oxidative DNA damage in human hepatoma and leukemia cells. The oxidative damage was size-dependent, being 90 nm AuNPs slightly more genotoxic than 30 and 50 nm AuNPs. 30 nm AuNPs did not exhibit any mutagenic or recombinogenic activity in Drosophila.